Resistance of Islamist groups to government policies in the settlement of religious radicalism - Hendri, Novi; Qudsy, Saifuddin; Elvira, Maiza; Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The topic of eradicating and preventing religious radicalism is quite a heavy homework for the Indonesian government. This article discusses the rejection and resistance of Islamic groups who are quite strong against the government's efforts to eradicate and prevent religious radicalism. The resistance has abandoned the classical pattern which is synonymous with violence, and started using strategies that are more easily accepted by society; digital utilization by using social media, and websites to spread their doctrine. Many people are affected, especially young people whose fighting spirit is still very high. This is based on research that the author conducted in 2018 and 2022. This research is the realm of Islamic studies studies, the instrument used in this research is in-depth interviews with the informants involved. The results of the research show that the rejection of Islamist groups occurs in various forms: both soft and hard. Soft rejection occurs through digital spaces, in the form of social-religious movements: recitals or lectures as well as mastery of mosque management. While hard or open rejection, in the form of demonstrations to reject government policies.